ELEMEN-ELEMEN KOMUNIKASI DALAM KONTEN REVIEW FILM HOME SWEET LOAN di AKUN @ngelantur¬¬¬¬¬¬_id - Syabina Nur Syania; Sutisna Riyanto; Erna Ernawati (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
Communication is a process by which one person conveys information and understanding to another. Film is a communication medium that has a significant impact on shaping public opinion. Film is not just a means of entertainment, but also a medium for education and social reflection. TikTok, as a communication medium for delivering messages, can reach Generation Z audiences. The purpose of the communication process carried out by the @ngelantur_id account through the Home Sweet Loan film review content is to provide information, understanding, and build audience interest in the film being discussed. This study aims to determine the communication elements in the Home Sweet Loan film review content on the @ngelantur_id account. The TikTok account @ngelantur_id utilizes a relaxed, humorous, and analytical style of messaging, including visual articles about Generation Z. The communication process is used as an analysis to assess the recipient's interest in the Home Sweet Loan film review content. The elements that support the communication process are